Il Lykion e la conservazione della sua identità: da Dioscoride a Maimonide e alle soglie dell'età contemporanea. - Taborelli, Luigi (Scripta Classica Israelica, 2024)
A journey through time, between archaeology, philology, pharmacology and botany, but also through space, from the Mediterranean Sea to India, following the trade of a very special commodity. This is how the author's journey in search of information on the identity of a valuable medicine can be summarised. In far-flung markets based on traditional trade skills and customs, the preservation of a commodity's name and its recognisability were essential to ensure the survival of the commodity itself and the culture it carried. Knowledge of the properties of the Lykion medicine known to the encyclopaedists and physicians of the Greco-Roman era can be traced back to Jewish and Islamic culture and up to the dawn of the contemporary age.